The contribution of local outdoor recreational services to the sustainable management of environmental resources: the case of Tabor Mountain Recreational Park in Hawassa City, Ethiopia. Issue 1 (9th December 2022) - Mellaku, Meselu Tegenie; Melka, Yoseph; Ayenew, Bamlaku; Teshale Taye, Tirusew; Tilahun, Abera
Abstract: There has to date been limited research on the economic valuation of local outdoor recreational services to inform policy and practice. This study attempts to fill this gap by estimating the annual recreational value of Tabor Mountain Recreational Park, an open-access recreational site in Hawassa City (also known as Awassa City), Ethiopia. This study employs single-bounded dichotomous choice and open-ended elicitation methods using primary and secondary data collected from 260 urban residents during June–August 2019. A complementary assessment of the determinants of local visitors' willingness-to-pay (WTP) is also carried out. Descriptive statistics and a binary logistic regression model were used to analyze the survey data. Overall, 87% and 98% of the respondents were willing to accept the initial bid value and to give non-zero maximum WTP, respectively. On average, a local resident makes/intends to make 2.57 visits per month paying a mean entrance fee of ETB 28.33 per visit, which represents approximately ETB 93, 498, 000 per year. Furthermore, average monthly income and the afternoon visiting-time preference of local visitors had a positive effect on individuals' WTP. Initial bid value, frequency of visits per month, number of dependent families, and age of local visitors had a negative effect on WTP. The substantial annual local recreational value estimate of Tabor Mountain Park reveals the potential of local financing alternatives for sustainable development and management of environmental resources in similar settings.